2023
DOI: 10.1038/s41467-023-39683-z
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic viruses engineered to enforce cholesterol efflux restore tumor-associated macrophage phagocytosis and anti-tumor immunity in glioblastoma

Abstract: The codependency of cholesterol metabolism sustains the malignant progression of glioblastoma (GBM) and effective therapeutics remain scarce. In orthotopic GBM models in male mice, we identify that codependent cholesterol metabolism in tumors induces phagocytic dysfunction in monocyte-derived tumor-associated macrophages (TAMs), resulting in disease progression. Manipulating cholesterol efflux with apolipoprotein A1 (ApoA1), a cholesterol reverse transporter, restores TAM phagocytosis and reactivates TAM-T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Moreover, KRT14 expression has been implicated in MHC class II presentation in breast cancer [ 35 ], suggesting that down-regulation of KRT14 in TNBC could result in increased MHC II expression and facilitate the activation of CD4 + T cells. In our previous study [ 49 ], we discovered that the accumulation of cholesterol in tumor-associated macrophages (TAMs) significantly hinders the mitochondrial translation of TAMs, which ultimately impacts their phagocytic function. Conversely, the intratumoral injection of ADV-ApoA1 can reprogram the lipid metabolism of the GBM tumor microenvironment, modulate cholesterol efflux, restore TAMs’ phagocytosis, and reactivate TAM-T cell anti-tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, KRT14 expression has been implicated in MHC class II presentation in breast cancer [ 35 ], suggesting that down-regulation of KRT14 in TNBC could result in increased MHC II expression and facilitate the activation of CD4 + T cells. In our previous study [ 49 ], we discovered that the accumulation of cholesterol in tumor-associated macrophages (TAMs) significantly hinders the mitochondrial translation of TAMs, which ultimately impacts their phagocytic function. Conversely, the intratumoral injection of ADV-ApoA1 can reprogram the lipid metabolism of the GBM tumor microenvironment, modulate cholesterol efflux, restore TAMs’ phagocytosis, and reactivate TAM-T cell anti-tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated cholesterol metabolism in the glioblastoma microenvironment also promotes tumor progression and immunosuppression. Therefore, targeting the disordered cholesterol metabolism in GBM, Wang et al developed an oncolytic adenovirus loaded with the cholesterol reverse transporter apolipoprotein A1 (ApoA1), for the treatment of GBM, which restores macrophages phagocytosis by manipulating cholesterol efflux and reactivates anti-tumor immunity [ 89 ]. Dong et al found that in GBM, macrophages highly expressed 7-dehydrocholesterol reductase (DHCR7), increased cholesterol biosynthesis, and served as “cholesterol factory” supplying cholesterol for GBM growth.…”
Section: Therapeutic Strategies Targeting Metabolism Between Gams And...mentioning
confidence: 99%
“…It leads to Siglec-10 or PD-1 enhancement, resulting in loss of phagocytic capacity of TAMs. In addition, cholesterol accumulation impaired mitochondrial function in TAMs, and cholesterol-induced mitochondrial damage through the oxidation product 7-ketocholesterol could inhibit the phagocytosis of TAMs.ApoA1-mediated cholesterol efflux from TAMs can reduce mitochondrial damage and restore the phagocytosis of TAMs [ 25 ]. In summary, tumor cells promote cholesterol accumulation in the microenvironment.…”
Section: Reprogramming Of Lipid Metabolism In the Tumor Microenvironmentmentioning
confidence: 99%